2019
DOI: 10.1177/1071181319631488
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Visual Acuity and Contrast Sensitivity using Head-Mounted Displays in a Virtual Environment: A Pilot Study

Abstract: Virtual reality (VR) and personal head-mounted displays (HMDs) can be a viable tool for the presentation of scientifically accurate and valid demonstrative data in the courtroom. However, the capabilities and limitations of the technology need to be fully characterized. The current pilot study evaluated visual acuity and contrast sensitivity using two commercially available HMDs (Oculus Rift and HTC Vive Pro). Preliminary findings indicated that visual acuity and contrast sensitivity experienced in VR may be l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…It is also slightly higher than the threshold of 23.3% that we found when applying Dolhasz et al (2016) contrast offset threshold equation to our context. The difference may be the corollary of the poorer contrast sensitivity of observers using an HMD (Sproule et al, 2019). Yet, the value we measured seems to also indicate that perception is done through the peripheral vision field (Lee, 2004).…”
Section: Contrast Sensitivitymentioning
confidence: 65%
See 1 more Smart Citation
“…It is also slightly higher than the threshold of 23.3% that we found when applying Dolhasz et al (2016) contrast offset threshold equation to our context. The difference may be the corollary of the poorer contrast sensitivity of observers using an HMD (Sproule et al, 2019). Yet, the value we measured seems to also indicate that perception is done through the peripheral vision field (Lee, 2004).…”
Section: Contrast Sensitivitymentioning
confidence: 65%
“…Yet, we are unable to identify a functional threshold. We know that the contrast sensitivity of observers using an HMD is poorer than in a real environment (Sproule et al, 2019). Due to a limited range of displayed luminance (Ledda et al, 2004), chromatic aberrations, and insufficient resolution, it has been concluded that VR technology is not able to reproduce standard contrast sensitivity testing (Vivas-Mateos et al, 2020).…”
Section: Light and Contrast Sensitivitymentioning
confidence: 99%
“…The accuracy of this replication test was evaluated by comparing real-world trials between this study versus Sproule et al (2019). Two-sample unpaired t-tests assuming equal variances were performed across all visual acuity tests.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the Snellen, Landolt, and contrast charts were scaled to a test distance of 9ft, 10ft, and 10 ft, respectively. The depth perception tests conducted in Sproule et al (2019) were not replicated in this study.…”
Section: Experimental Designmentioning
confidence: 92%
See 1 more Smart Citation